Safety and Efficacy of Endovascular Therapy for Blood Blister-Like Aneurysms: Willis Covered Stents and Double Stents Assistant Coils—A Single Center Cohort Study - Chang, Hanxiao; Shen, Yuqi; Li, Zheng; Lin, Chao; Chen, Hua; Lu, Hua (Frontiers in Neurology, 2021)
Objective To summarise and discuss the application of Willis covered stents (WCSs) and double stent-assisted coils in the treatment of blood blister-like aneurysms (BBAs). Materials Of 21 patients suffering from BBAs, 12 were treated using WCSs from January 2015 to December 2019 and others were treated using double stents-assisted coils. The indications for treatment, perioperative findings, and postoperative follow-up results were collected and analysed. Results All 21 patients had successful deployment of stents. Complete occlusion of the aneurysm was achieved in all 12 patients immediately after deployment of 1 WCS. One mild vasospasm and 3 aggressive procedure related vasospasms happeded during the deployment of WCSs and a patient died with ipsilateral temporal lobe rebleeding at the sixth day after the deployment of the WCS. And a dissection was detected after the deployment of WCS. Neck remnants were observed in 2 patients treated with double stent-assisted coils. And 1 acute occlusion of ipsilateral MCA branch and 2 mild procedure related vasospasms occured intraoperationally treatment by double stents assistant coils. In the first postoperstive angiographic follow-up , all BBAs were completely occluded. Mild asymptomatic stent stenosis was observed in 2 patients treated with WCSs. Follow-up examination at 6 monthes after the employment of WCSs showed that the mRs score was 0 in 4 patients, 1 in 3 patients, 2 in 3 patients, 4 in 1 patient and 6 in 1 patient. And the examination results with double stents assistant coils showed that the mRs score was 0 in 2 patients, 1 in 4 patients, 2 in 2 patients, 4 in 1 patient. Conclusions The implementation of WCSs and double stent-assisted coils for the treatment of BBAs are both safe and efficient. WCSs provide a higher rate of immediate occlusion rate, however, there was no statistic difference during the long-term follow-up.